The Implementation of Tri Hita Karana Values in the Modern Work Culture of Great Value Medi Group - Dewi, Ni Luh Manik Cahyaning; Oktavia, Kartika; Antonius, Antonius (Syntax Corporation, 2025)
This study examines the implementation of the traditional Balinese philosophy Tri Hita Karana within the modern corporate work culture of Medi Group, a locally owned business in Bali. Employing a qualitative descriptive approach, this research explores how Tri Hita Karana, which emphasizes harmonious relationships between humans and God (Parahyangan), among humans (Pawongan), and between humans and nature (Palemahan), can be integrated into modern organizational practices. Data were collected through in-depth interviews with key informants, including the CEO and Chief Human Officer of Medi Group, supported by observations and document analysis. Using Edgar Schein’s Organizational Culture Theory, the study analyzes the cultural layers of the company, specifically through its core corporate values known as